A rare earth doped ceramic composite material and its preparation process

By preparing rare earth rubber and chlorite-based flame retardant in composite materials, the cross-linked network structure and lanthanum-phenanthroline complex is solved, and the high temperature stability, mechanical strength and flame retardant capacity of composite materials are improved.

CN119350839BActive Publication Date: 2025-03-25安徽广博机电制造股份有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411929977.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Ordinary composite materials have insufficient high temperature resistance in high temperature environments below 600°C, and their mechanical properties are generally and have no flame retardant ability.

Method used

Rare-earth doped ceramic composite materials are used to prepare rare earth rubber and chlorite-based flame retardant and added to the preparation process of the composite materials to form a cross-linked network structure to enhance mechanical properties, and the thermal stability and flame retardant ability are improved through the lanthanum-phenanthroline complex and phytic acid structure.

Benefits of technology

It realizes that the composite material plays a stable role in high temperature environment, is not easy to break and crack, and has a long service life, and has excellent high temperature resistance, mechanical strength and flame retardant ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350839B_ABST
    Figure CN119350839B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramic composite materials, and discloses a rare earth doped ceramic composite material and a preparation process thereof, wherein the rare earth doped ceramic composite material is composed of two parts, component A and component B; wherein component A comprises the following raw materials: polyether polyol, triethanolamine, dibutyltin dilaurate, rare earth rubber, chlorite-based flame retardant; and component B comprises the following raw materials: isophorone diisocyanate, feldspar powder, talcum powder, low melting point glass powder, and kaolin. The present invention prepares rare earth rubber and chlorite-based flame retardant and adds them to the preparation process of rare earth doped ceramic composite material, so that the prepared composite material has excellent high temperature resistance, mechanical strength and flame retardant ability, can stably play a role in high temperature environment, is not easy to be damaged and cracked, and has a long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic composite materials, and in particular to a rare earth doped ceramic composite material and a preparation process thereof. Background Art

[0002] With the development of materials science, materials with different properties are combined together to give full play to the advantages of each component material, while making up for the shortcomings to obtain composite materials with better performance. Polyurethane is an important polymer material obtained by polymerization reaction of raw materials such as isocyanate and polyol. It has excellent insulation, flexibility and processability, and is widely used in many fields. In the preparation of composite materials, polyurethane materials are usually used as matrix materials and compounded with other materials to form composite materials with better performance. However, due to the easy thermal decomposition reaction of the polyurethane matrix under high temperature environment, the thermal stability of polyurethane composite materials is poor, which makes it difficult to meet the use requirements under high temperature environment. The mechanical strength of the polyurethane material itself is insufficient and it does not have flame retardant properties. It is easy to be damaged during long-term use, which affects the service life of the composite material. At the same time, there are safety hazards.

[0003] In order to solve the above problems, the patent with announcement number CN107286637B discloses a low-smoke halogen-free flame retardant ceramic thermoplastic polyurethane elastomer composite material and its preparation method and application. The thermoplastic polyurethane elastomer composite material prepared by this patent has good flame retardant effect, low smoke density, high strength, good flexibility, high elongation at break, and can form a dense ceramic product in the range of 600-1000℃. The ceramic forming temperature is low and the ceramic forming is dense. The formed ceramic product has good high temperature strength and resistance to heat flow shock. However, the composite material prepared by this patent fails to form a ceramic structure in a high temperature environment below 600℃, and the high temperature resistance performance still needs to be improved. Summary of the invention

[0004] The purpose of the present invention is to provide a rare earth doped ceramic composite material and its preparation process, which solves the problem that the high temperature resistance of ordinary composite materials in high temperature environments below 600°C still needs to be improved and the problem that ordinary composite materials have general mechanical properties and do not have flame retardant ability.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A rare earth doped ceramic composite material, consisting of two parts: component A and component B; the component A comprises the following raw materials in parts by weight: 60-80 parts of polytetramethylene glycol, 1-3 parts of triethanolamine, 3-5 parts of dibutyltin dilaurate, 12-15 parts of rare earth rubber, and 6-8 parts of chlorite-based flame retardant; the component B comprises the following raw materials in parts by weight: 20-30 parts of isophorone diisocyanate, 3-5 parts of feldspar powder, 5-6 parts of talc powder, 5-8 parts of low melting point glass powder, and 3-5 parts of kaolin;

[0007] The preparation method of the rare earth rubber comprises the following steps:

[0008] S1: mixing epoxidized natural rubber and 1,10-phenanthroline-5-amino in toluene and heating the mixture to obtain phenanthroline rubber;

[0009] S2: Mixing phenanthroline rubber and lanthanum chloride solution in dimethyl sulfoxide, heating and stirring to obtain rare earth rubber;

[0010] In this scheme, the epoxy group in the epoxidized natural rubber structure undergoes a ring-opening reaction with the amino group in the 1,10-phenanthroline-5-amino structure to obtain a phenanthroline rubber, and then the two phenanthroline nitrogen atoms in the phenanthroline rubber structure act as coordinating atoms to produce a coordination effect with the lanthanum ions in the lanthanum chloride solution to form a lanthanum-phenanthroline complex, thereby obtaining a rare earth rubber. The rare earth rubber structure has multiple hydroxyl groups and can participate in the preparation process of the composite material. The rare earth rubber polymer chain segment and the polymer chain segment of the composite material are entangled with each other to form a cross-linked network structure, thereby enhancing the mechanical properties of the composite material. At the same time, the lanthanum-phenanthroline complex formed in its structure can effectively improve the thermal stability and mechanical strength of the composite material molecules, so that it can stably function in a high temperature environment and is not easy to be damaged and cracked, so that it has a long service life;

[0011] The preparation method of the chlorite-based flame retardant comprises the following steps:

[0012] SS1: Place chlorite and D-methionine in N,N-dimethylformamide, heat and stir thoroughly, filter, wash and dry to obtain modified chlorite;

[0013] SS2: Place the modified chlorite in deionized water, ultrasonically disperse it for 10-15 minutes, add phytic acid, heat and stir, filter, wash and dry to obtain a chlorite-based flame retardant.

[0014] In this scheme, at high temperature, the carboxyl group in the D-methionine structure interacts with the hydroxyl group on the surface of chlorite to obtain a modified chlorite containing an amino group on the surface, and then the amino group on the surface of the modified chlorite interacts with the phosphate group in the phytic acid structure, and the phytic acid is coated on the surface of the chlorite to form a chlorite-based flame retardant. After the surface of the chlorite-based flame retardant is coated with phytic acid, it has good dispersibility in the composite matrix, is evenly distributed in the composite matrix, and plays a physical barrier role, which can not only enhance the mechanical properties of the composite material, but also prevent the flame from directly contacting the inside of the material when a fire occurs, effectively slow down the spread of the flame, and improve the flame retardant ability of the material. At the same time, the phytic acid structure coated on its surface contains a large number of phosphate groups, and the phytic acid decomposes at high temperature to produce gas. The release of gas can take away heat, reduce the temperature of the surface of the material, and slow down the combustion process. In addition, the surface also contains nitrogen elements, which can produce a synergistic effect with phytic acid to jointly enhance the flame retardant ability of the composite material, so that it can have an excellent flame retardant effect.

[0015] Furthermore, in step S1, the temperature of the temperature-raising reaction is 75-80° C. and the time is 3-5 hours.

[0016] Furthermore, in step S2, the temperature of the heating and stirring is 70-75° C., and the time is 5-6 hours.

[0017] Furthermore, in step S2, the mass fraction of the lanthanum chloride solution is 15-20%.

[0018] Furthermore, in step SS1, the average particle size of the chlorite is 30 μm.

[0019] Furthermore, in step SS1, the temperature for sufficient stirring after heating is 90-95° C., the stirring speed is 300-350 r / min, and the stirring time is 3-5 h.

[0020] Furthermore, in step SS2, the temperature of the heating and stirring is 55-65° C., and the time is 5-6 hours.

[0021] A preparation process of a rare earth-doped ceramic composite material comprises the following steps:

[0022] Step 1: taking polytetramethylene glycol, triethanolamine, dibutyltin dilaurate, rare earth rubber, and chlorite-based flame retardant, mixing and stirring to obtain component A;

[0023] Step 2: fully mix isophorone diisocyanate, feldspar powder, talc powder, low melting point glass powder and kaolin at a speed of 250-300 r / min for 1-1.5 h to obtain component B;

[0024] Step 3: After fully mixing component A and component B, pour them into a mold for foaming treatment for 0.5-1h, cool them naturally to room temperature, and then demould and take them out to obtain a composite material.

[0025] Furthermore, it is characterized in that, in step 1, the rotation speed of the mixing and stirring is 300-350r / min, and the time is 20-30min.

[0026] Furthermore, it is characterized in that, in step three, the mold temperature of the mold is 40-45°C.

[0027] Beneficial effects of the present invention:

[0028] The present invention prepares rare earth rubber and chlorite-based flame retardants and adds them to the preparation process of rare earth-doped ceramic composite materials, so that the prepared composite materials have excellent high temperature resistance, mechanical strength and flame retardancy, can function stably in high temperature environments, are not easily damaged or cracked, and have a long service life.

[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0031] Figure 1 The zeta potential diagram of the modified chlorite and the chlorite-based flame retardant of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The preparation methods of rare earth rubber and chlorite-based flame retardants in the following examples and comparative examples of the present invention are as follows:

[0034] 1. Preparation of rare earth rubber

[0035] S1: 3 g of epoxidized natural rubber was placed in 50 ml of toluene, and after sufficient mixing and stirring, 2.6 g of 1,10-phenanthroline-5-amino was added, and the temperature was raised to 75° C. for reaction for 3 h. The product was collected after reduced pressure distillation, i.e., phenanthroline rubber;

[0036] S2: Place 3.5 g of phenanthroline rubber in 60 ml of dimethyl sulfoxide, mix and stir thoroughly, then add 5 ml of 15% by mass lanthanum chloride solution, heat to 70°C, stir for 5 hours, collect the product after stirring, and obtain rare earth rubber.

[0037] The rare earth content in rare earth rubber was tested using the EDTA titration method. The specific steps are as follows: weigh 1g of rare earth rubber as a sample and place it in a beaker, add a 30% volume fraction hydrochloric acid solution, stir and mix thoroughly, transfer to a 100ml volumetric flask, dilute to volume with distilled water, transfer 10ml of the test solution into a conical flask, add a 35% volume fraction acetic acid-sodium acetate buffer solution to adjust the pH to 5, add 2 drops of xylenol orange indicator, and titrate the solution with a 0.1mol / L EDTA standard solution until the color of the solution changes and reaches the titration endpoint, record the volume of EDTA consumed, and calculate according to the following formula: mass fraction of rare earth in rare earth rubber = (EDTA standard solution concentration × consumed EDTA standard solution volume × molar mass of rare earth ions) × 100% / sample mass; after calculation, the rare earth content in rare earth rubber is 10.4%.

[0038] 2. Preparation of chlorite-based flame retardant

[0039] SS1: 3.5 g of chlorite with an average particle size of 30 μm and 3 g of D-methionine were placed in 80 ml of N,N-dimethylformamide, heated to 90 °C, set the speed to 300 r / min and stirred for 3 h. After the mixture was filtered, washed and dried, the modified chlorite was obtained.

[0040] SS2: 3.8 g of modified chlorite was placed in 100 ml of deionized water, and after ultrasonic dispersion for 10 min, 3.2 g of phytic acid was added, the temperature was raised to 55 °C and stirred for 5 h, and the chlorite-based flame retardant was obtained after filtering, washing and drying.

[0041] The potential values ​​of modified chlorite and chlorite-based flame retardant were tested using a zeta potential meter. Figure 1 It can be seen that the potential value of modified chlorite is 2.4mv; the potential value of chlorite-based flame retardant is -1.9mv; the positive potential value of modified chlorite is due to the positively charged amino groups on its surface, while the negative potential value of chlorite-based flame retardant is due to the surface of modified chlorite being coated with negatively charged phytic acid.

[0042] Example 1

[0043] Preparation of composite materials

[0044] Step 1: Take 60 parts of polytetramethylene glycol, 1 part of triethanolamine, 3 parts of dibutyltin dilaurate, 12 parts of rare earth rubber, and 6 parts of chlorite-based flame retardant, set the stirring speed to 300 r / min, stir for 20 minutes, and mix thoroughly to obtain component A;

[0045] Step 2: 20 parts of isophorone diisocyanate, 3 parts of feldspar powder, 5 parts of talc, 5 parts of low-melting point glass powder and 3 parts of kaolin were fully mixed at a speed of 250 r / min for 1 hour to obtain component B;

[0046] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 40° C. for foaming for 0.5 h, and then naturally cool to room temperature and demould to obtain a composite material.

[0047] Example 2

[0048] Preparation of composite materials

[0049] Step 1, take 70 parts of polytetramethylene glycol, 2 parts of triethanolamine, 4 parts of dibutyltin dilaurate, 14 parts of rare earth rubber, and 7 parts of chlorite-based flame retardant, set the stirring speed to 320 r / min, stir for 25 minutes, and mix thoroughly to obtain component A;

[0050] Step 2: 25 parts of isophorone diisocyanate, 4 parts of feldspar powder, 5.5 parts of talc, 6 parts of low-melting point glass powder and 4 parts of kaolin were fully mixed at a speed of 280 r / min for 1.2 h to obtain component B;

[0051] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 43° C. for foaming for 0.8 h, and then naturally cool to room temperature and demould to obtain a composite material.

[0052] Example 3

[0053] Preparation of composite materials

[0054] Step 1, take 80 parts of polytetramethylene glycol, 3 parts of triethanolamine, 5 parts of dibutyltin dilaurate, 15 parts of rare earth rubber, and 8 parts of chlorite-based flame retardant, set the stirring speed to 350r / min, stir for 30min, and mix thoroughly to obtain component A;

[0055] Step 2: 30 parts of isophorone diisocyanate, 5 parts of feldspar powder, 6 parts of talc, 8 parts of low-melting point glass powder and 5 parts of kaolin were fully mixed at a speed of 300 r / min for 1.5 hours to obtain component B;

[0056] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 45° C. for foaming treatment for 1 hour, and then naturally cool to room temperature and demould to obtain a composite material.

[0057] Comparative Example 1

[0058] Preparation of composite materials

[0059] Step 1, take 70 parts of polytetramethylene glycol, 2 parts of triethanolamine, 4 parts of dibutyltin dilaurate, and 7 parts of chlorite-based flame retardant, set the stirring speed to 320 r / min, stir for 25 minutes, and mix thoroughly to obtain component A;

[0060] Step 2: 25 parts of isophorone diisocyanate, 4 parts of feldspar powder, 5.5 parts of talc, 6 parts of low-melting point glass powder and 4 parts of kaolin were fully mixed at a speed of 280 r / min for 1.2 h to obtain component B;

[0061] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 43° C. for foaming for 0.8 h, and then naturally cool to room temperature and demould to obtain a composite material.

[0062] Comparative Example 2

[0063] Preparation of composite materials

[0064] Step 1, take 70 parts of polytetramethylene glycol, 2 parts of triethanolamine, 4 parts of dibutyltin dilaurate, and 14 parts of rare earth rubber, set the stirring speed to 320r / min, stir for 25min, and mix thoroughly to obtain component A;

[0065] Step 2: 25 parts of isophorone diisocyanate, 4 parts of feldspar powder, 5.5 parts of talc, 6 parts of low-melting point glass powder and 4 parts of kaolin were fully mixed at a speed of 280 r / min for 1.2 h to obtain component B;

[0066] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 43° C. for foaming for 0.8 h, and then naturally cool to room temperature and demould to obtain a composite material.

[0067] Comparative Example 3

[0068] Preparation of composite materials

[0069] Step 1, take 70 parts of polytetramethylene glycol, 2 parts of triethanolamine, 4 parts of dibutyltin dilaurate, 14 parts of phenanthroline rubber, and 7 parts of chlorite-based flame retardant, set the stirring speed to 320 r / min, stir for 25 minutes, and mix thoroughly to obtain component A;

[0070] Step 2: 25 parts of isophorone diisocyanate, 4 parts of feldspar powder, 5.5 parts of talc, 6 parts of low-melting point glass powder and 4 parts of kaolin were fully mixed at a speed of 280 r / min for 1.2 h to obtain component B;

[0071] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 43° C. for foaming for 0.8 h, and then naturally cool to room temperature and demould to obtain a composite material.

[0072] Comparative Example 4

[0073] Preparation of composite materials

[0074] Step 1: Take 70 parts of polytetramethylene glycol, 2 parts of triethanolamine, 4 parts of dibutyltin dilaurate, 14 parts of rare earth rubber, and 7 parts of modified chlorite, set the stirring speed to 320 r / min, stir for 25 minutes, and mix thoroughly to obtain component A;

[0075] Step 2: 25 parts of isophorone diisocyanate, 4 parts of feldspar powder, 5.5 parts of talc, 6 parts of low-melting point glass powder and 4 parts of kaolin were fully mixed at a speed of 280 r / min for 1.2 h to obtain component B;

[0076] Step 3: After fully mixing component A and component B, pour them into a mold at a mold temperature of 43° C. for foaming for 0.8 h, and then naturally cool to room temperature and demould to obtain a composite material.

[0077] Performance Testing

[0078] The composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were made into samples that met the specifications, and the samples were tested for flame retardancy with reference to the UL-94 standard; the samples were tested for Vicat softening temperature with reference to the GB / T1633-2000 standard to determine the high temperature resistance of the samples; the samples were tested for tensile strength with reference to the GB / T1040.2-2022 standard to determine the mechanical strength of the samples; the specific test results are shown in the following table:

[0079]

[0080] It can be seen from the above table that the samples prepared in Examples 1 to 3 all have excellent flame retardant properties, high temperature resistance and mechanical strength. In the sample prepared in Comparative Example 1, no rare earth rubber was added, and the high temperature resistance was poor, but a chlorite-based flame retardant was added thereto, so it had an excellent flame retardant effect. In the sample prepared in Comparative Example 2, no chlorite-based flame retardant was added, so the flame retardant performance was average, but rare earth rubber was added thereto, and the high temperature resistance was good. In the sample prepared in Comparative Example 3, no rare earth rubber was added, and phenanthroline rubber was directly added, and the high temperature resistance effect was average. Since a chlorite-based flame retardant was also added thereto, it had an excellent flame retardant effect. In the sample prepared in Comparative Example 4, modified chlorite and rare earth rubber were directly added, and the high temperature resistance and mechanical properties were excellent, and the flame retardant performance needed to be improved.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0082] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A rare earth doped ceramic composite material, characterized in that: The invention is composed of two parts: component A and component B; the component A comprises the following raw materials in parts by weight: 60-80 parts of polytetramethylene glycol, 1-3 parts of triethanolamine, 3-5 parts of dibutyltin dilaurate, 12-15 parts of rare earth rubber, and 6-8 parts of chlorite-based flame retardant; the component B comprises the following raw materials in parts by weight: 20-30 parts of isophorone diisocyanate, 3-5 parts of feldspar powder, 5-6 parts of talc powder, 5-8 parts of low-melting-point glass powder, and 3-5 parts of kaolin; The preparation method of the rare earth rubber comprises the following steps: S1: 3 g of epoxidized natural rubber and 2.6 g of 1,10-phenanthroline-5-amino are mixed in 50 ml of toluene and then heated to react to obtain phenanthroline rubber; S2: 3.5 g of phenanthroline rubber and 5 ml of 15% by mass lanthanum chloride solution were mixed in 60 ml of dimethyl sulfoxide, and the mixture was heated and stirred to obtain rare earth rubber; The preparation method of the chlorite-based flame retardant comprises the following steps: SS1: 3.5 g of chlorite and 3 g of D-methionine were placed in 80 ml of N,N-dimethylformamide, heated and stirred thoroughly, and then filtered, washed and dried to obtain modified chlorite; SS2: 3.8 g of modified chlorite was placed in 100 ml of deionized water, and after ultrasonic dispersion for 10-15 min, 3.2 g of phytic acid was added, the temperature was raised and stirred, and the chlorite-based flame retardant was obtained after filtering, washing and drying.

2. The rare earth doped ceramic composite material according to claim 1, characterized in that: In step S1, the temperature of the temperature-raising reaction is 75-80°C and the time is 3-5h.

3. The rare earth-doped ceramic composite material according to claim 1, characterized in that: In step S2, the temperature of the heating and stirring is 70-75°C and the time is 5-6h.

4. The rare earth-doped ceramic composite material according to claim 1, characterized in that: In step SS1, the average particle size of the chlorite is 30 μm.

5. The rare earth doped ceramic composite material according to claim 1, characterized in that: In step SS1, the temperature for sufficient stirring after heating is 90-95° C., the stirring speed is 300-350 r / min, and the stirring time is 3-5 h.

6. The rare earth-doped ceramic composite material according to claim 1, characterized in that: In step SS2, the temperature of the heating and stirring is 55-65° C., and the time is 5-6 hours.

7. A process for preparing the rare earth-doped ceramic composite material as claimed in claim 1, characterized in that: The following steps are involved: Step 1: taking polytetramethylene glycol, triethanolamine, dibutyltin dilaurate, rare earth rubber, and chlorite-based flame retardant, mixing and stirring to obtain component A; Step 2: fully mix isophorone diisocyanate, feldspar powder, talc powder, low melting point glass powder and kaolin at a speed of 250-300 r / min for 1-1.5 h to obtain component B; Step 3: After fully mixing component A and component B, pour them into a mold for foaming treatment for 0.5-1h, cool them naturally to room temperature, and then demould and take them out to obtain a composite material.

8. The process for preparing a rare earth-doped ceramic composite material according to claim 7, characterized in that: In step 1, the mixing and stirring is carried out at a speed of 300-350 r / min and for a time of 20-30 min.

9. The process for preparing a rare earth-doped ceramic composite material according to claim 7, characterized in that: In step 3, the mold temperature of the mold is 40-45°C.

Citation Information

Patent Citations

  • A low-smoke, halogen-free, flame-retardant, ceramizable thermoplastic polyurethane elastomer composite material, its preparation method, and its application.

    CN107286637B

  • Polyurethane resin with self-early warning function and preparation method thereof

    CN117964875A

  • High-strength fireproof polyurethane and preparation method thereof

    CN118480167A